2009
DOI: 10.1210/en.2008-1584
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Ovary-Specific Acidic Protein in Steroidogenic Tissues: A Possible Role in Steroidogenesis

Abstract: Ovary-specific acidic protein (OSAP) is a novel molecule discovered from a genomic project designed to identify ovary-selective genes in mice. Whereas public databases suggest extraovarian expression of OSAP, its tissue distribution has not yet been well documented. Thus, the expression profile of mouse and human OSAP was determined by quantitative real-time RT-PCR using RNAs isolated from various tissues. The results demonstrate that the human and mouse OSAP expression profiles are similar; OSAP is prominentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
3
12
0
Order By: Relevance
“…The reciprocal relationship between U17 snoRNA and HUMMR mRNA abundance in the developing mouse ovary suggests that the U17 snoRNA-HUMMR pathway may play a role in regulating steroid hormone production and postnatal gonadal maturation. Enrichment of HUMMR in steroidogenic tissues and its regulation under hypothalamic-pituitary-gonadal axis is consistent with such a role (Matsumoto et al, 2009; Zhou et al, 2011). Our findings that the developmental decline in U17 snoRNA expression is concomitant with the de-repression of HUMMR expression and the steroidogenic demand, and that in vivo knockdown of U17 snoRNA increases HUMMR expression and steroid synthesis, implicates U17 snoRNA as an upstream regulator that modulates mitochondrial cholesterol import.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The reciprocal relationship between U17 snoRNA and HUMMR mRNA abundance in the developing mouse ovary suggests that the U17 snoRNA-HUMMR pathway may play a role in regulating steroid hormone production and postnatal gonadal maturation. Enrichment of HUMMR in steroidogenic tissues and its regulation under hypothalamic-pituitary-gonadal axis is consistent with such a role (Matsumoto et al, 2009; Zhou et al, 2011). Our findings that the developmental decline in U17 snoRNA expression is concomitant with the de-repression of HUMMR expression and the steroidogenic demand, and that in vivo knockdown of U17 snoRNA increases HUMMR expression and steroid synthesis, implicates U17 snoRNA as an upstream regulator that modulates mitochondrial cholesterol import.…”
Section: Discussionsupporting
confidence: 73%
“…HUMMR is highly expressed in steroidogenic tissues and is regulated by the hypothalamic-pituitary-gonadal axis in mice (Matsumoto et al, 2009; Zhou et al, 2011). Since cholesterol is an obligate precursor for mitochondrial steroid synthesis, we examined the U17 snoRNA-HUMMR pathway in steroidogenic tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Hypoxia-up-regulated mitochondrial movement regulator (HUMMR) was termed corneal endothelium-specific protein-1 in corneal endothelium, potentially maintaining mitochondrial abundance and morphology [10]. It has recently been demonstrated that HUMMR, expressed in neurons, astrocytes and even whole brain, is closely associated with mitochondrial movement and mainly regulates mitochondrial distribution and transport [11].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have demonstrated that MGARP is highly expressed in the inner segment of the photoreceptor (IS), outer plexiform layer (OPL) and ganglion cell layer (GCL) of the retina, which are enriched with mitochondria [3]. Additional studies have indicated that MGARP is involved in steroidogenesis through its ability to maintain mitochondrial abundance and morphology, and importantly, it is also highly expressed in the organs involved in steroidogenesis, such as the ovary, testis, adrenal gland and brain [4], [5]. MGARP can also be induced by HIF-1 and hypoxia, biasing mitochondrial transport in the anterograde direction and joining the mitochondrial dance [6], [7].…”
Section: Introductionmentioning
confidence: 99%